Leksykografia Andrzeja Calagiusa. Uwagi wstępne - Jankowiak, Lucyna Agnieszka (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The aim of this article is to review the lexicography of Andrzej Calagius, to present a list of his dictionaries of synonyms and to correct the misinformation about his dictionaries. The article describes three German-Polish-Latin editions (1579, 1595, 1602), one German-Latin edition (1597), and two Latin editions (1592 and 1594). It also proves that these multilingual editions are not revised versions of the 1579 edition but independent dictionaries.